Analisis Kelayakan Pertanian Perkotaan dan Peran dalam Mendukung Pemberdayaan Perempuan: Studi Kasus di Cengkareng Barat dan Duri Kosambi - Azzahrah, Salwa Yasyifa; Sulistyowati, Lies (Universitas Galuh, 2026)
Urban agriculture is the practice of carrying out agricultural activities within urban areas. Projects serve as one of the tools to address economic, social, and environmental challenges occurring in cities. More specifically, urban farming projects are implemented to enhance food supply in urban areas, improve environmental quality, and empower local communities. The urban farming program in DKI Jakarta Province is guided by the “Desain Besar Pertanian Perkotaan tahun 2018-2030”, which sets the target of utilizing 30% of green open space for productive purposes and fulfilling 30% of the demand for vegetables through local production. This study aims to analyze the implementation of urban farming projects by assessing their financial and economic feasibility, as well as identifying their role in supporting women’s empowerment in Cengkareng Barat and Duri Kosambi sub-districts. The research employs descriptive analysis, cost benefit analysis (CBA), and the Likert scale. The results indicate that urban agriculture programs in Kelurahan Cengkareng Barat dan Duri Kosambi have been implemented in accordance with local government policies, although challenges remain. Financial and economic feasibility analysis shows that the programs are viable, with positive Net Present Value (NPV) and a Benefit-Cost Ratio (BCR) greater than one, meaning that the benefits outweigh the costs. Socially, urban agriculture contributes significantly to women’s empowerment by providing additional income, enhancing technical skills, building self-confidence, and encouraging active participation in community groups. It also strengthens women’s roles in environmental sustainability through eco-friendly farming practices.